Empirische Zugänge zu Heurismen und geistiger Beweglichkeit in den Problemlöseprozessen von Fünft- und Sechstklässlern (mathematica didactica, 2018)
The use of heuristic techniques is considered to be an important aspect of (mathematical) problem solving – there are no theoretical doubts about that. But how can heuristics be identified in empirical processes and how do they correlate to success or failures in those processes? After a theoretical discussion of the term “heuristics” and its connection to mental flexibility, the development of a coding manual to identify heuristics in empirical processes validly and objectively using processes by university students is described. The goal is to analyze the influence of heuristics on the problem solving attempts of fifth and sixth graders as well as its relation to mental flexibility. Therefore, qualitative analyses of pupils’ problem solving processes are presented. Some of the successful pupils (especially successful participants of mathematical competitions) use less heuristics than the other participants of the study. A possible explanation for this result is a higher mental flexibility of those pupils.
Keywords: Problem Solving, Heuristics, Mental Flexibility